Maternal Healthcare Utilization among Mothers Aged 15-24 Years in Indonesia: a Literature Review - Mabda Novalia Istafa; Ferry Efendi; Erna Dwi Wahyuni (Universitas Airlangga, 2021)
Introduction: The use of health care services in mothers was a very important concern in developing countries because it was very beneficial in terms of declining maternal mortality rate, but the use of maternal health services in mothers aged 15-24 years In Indonesia was still not maximized. The purpose of this review was to analyze best practices in the use of maternal health services in mothers aged 15-24 years.Method: The systematic review of this search was done by the publication range was five years ago. Article criteria were articles reviewed by Bestari Partners, government documents and research locations in developing countries. Acquired 10 references that meet predefined criteria.Results: The analysis obtained was the use of maternal health services in mothers aged 15-24 years needs to be increased by looking at the factors that influence among them were seeing from the socio-demography of mothers and husbands, household factors, access to health services and regional factors.Conclusion: These recommendations are aimed at governments, health professionals and families that efforts to increase not only can be done by a single community line, but the whole must also be able to cooperate by the role in the efforts to increase the use of Health care services.